FAKTOR-FAKTOR YANG MEMENGARUHI PENDAPATAN PEDAGANG IKAN SEGAR DI PASAR AGROPOLITAN WAIMITAL KABUPATEN SERAM BAGIAN BARAT - Ruban, Angela; Bawole, Dionisius; Wattimena, Nelma; Kaya, Ivonne Raystika Gretha (PAPALELE (Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan), 2024)
West Seram is a regency in Maluku Province that is part of fisheries management area (WPP) 715. The West Seram sea area has significant potential fisheries resources, estimated at 1,083,360 tons per year. The Waimital Agropolitan Market, located in Kairatu District, West Seram Regency, is the major market utilized by traders from various villages such as Pakarena Hamlet, Waitasi, Pelitajaya, Waisarisa Village, Waesamu, and neighboring areas to sell or market fresh fish. This is a traditional market that trades a variety of things needed by the community, such as fishery products, agricultural, livestock, and other industrial products. Fresh fish items are the dominant fishery products in the Waimital Agropolitan market. This study uses a survey strategy with 40 participants. Data analysis uses quantitative descriptive analysis to compute the income of fresh fish traders and multiple linear regression analysis to evaluate the factors influencing fresh fish traders' income. The analysis revealed that the respondents of fresh fish sellers had an average monthly income of IDR 4.703.089, and the factor that influenced the income was capital (X4).